Cost-Oriented Agile Innovation for Mechatronics Management in Less Developed Regions. Issue 24 (2015) - Shala, Muzafer; Hajrizi, Edmond; Hoxha, Valmir; Stapleton, Larry
Abstract: Cost-oriented automation has a long tradition in IFAC and attracts a lot of attention in literatures associated, for example, with business process improvement. Whilst process-oriented cost reduction (such as LEAN for example) have been widely disseminated, in recent years practical cost-oriented solutions for automatic processes have not been reported so much in the literature. This is surprising given the increasing constraints upon, for example, manufacturing organisations in less developed peripheral regions. This paper re-energises the cost-oriented automation discourse by presenting projects which have used low-cost digital solutions to achieve potentially excellent results. The main contribution of the paper is to demonstrate practical applications of cost-oriented thinking in contexts where practical, cost-oriented automatic control are essential, such as post-conflict developing regions.